Infection-related hospitalisation in young adults with systemic lupus erythematosus: data from the National Inpatient Sample - Christina Chambers; Rashmi Dhital; Dilli R Poudel (Lupus Science and Medicine, 2023)
Introduction Care of young adults with SLE (YA-SLE, 18–24 years) is challenging due to major life transitions co-occurring with chronic healthcare needs. Studies have demonstrated poorer outcomes in the post-transition period. Epidemiological studies focused on serious infection-related hospitalisation (SIH) in YA-SLE are lacking.Methods We used National Inpatient Sample from 2010 to 2019 to study the epidemiology and outcomes of SIH for five common infections in SLE, namely sepsis, pneumonia, urinary tract infections, skin and soft tissue infections, and opportunistic infections. For time trends, we extended the dataset to cover 2000–2019. The primary outcome was the rate of SIH in YA-SLE compared with adults (25–44 years) with SLE and with young adults without SLE (YA-no SLE).Results From 2010 to 2019, we identified 1 720 883 hospital admissions with SLE in patients aged ≥18 years. Rates of SIH were similar in young adults and adults with SLE (15.0% vs 14.5%, p=0.12), but considerably higher than in the YA-no SLE group (4.2%, p<0.001). Among SLE with SIH, sepsis followed by pneumonia was the most common diagnosis. Significantly higher proportions of SIH among young adults than adults with SLE were comprised of non-white patients, belonged to the lowest income quartile and had Medicaid. However, only race/ethnicity was associated with SIH among YA-SLE. There was a higher prevalence of comorbid lupus nephritis and pleuritis among young adults compared with adults with SLE and SIH, and both comorbidities were associated with SIH in YA-SLE. Increasing rates of SIH, driven by sepsis, were seen over time.Discussion YA- SLE had similar rates of SIH to adults with SLE. While hospitalised YA-SLE differed sociodemographically from SLE adults and YA-no SLE, only race/ethnicity was associated with SIH in the YA-SLE group. Lupus nephritis and pleuritis were associated with higher SIH in YA-SLE. Among SLE with SIH, increasing trends of sepsis deserve further study.